DYES IN FOOD AND DRUGS ARE POTENTIAL IMMUNOMODULATORS - N. S. Aliakhnovich (SPb RAACI, 2019)
There are some data about various immunopathology effects of food dyes. Their use in food and medicines may induce hypersensitivity, which is regarded as a side effect of drugs or intolerance to food substances. Evaluation of the effect caused by food and drugs colorants on the immunity was conducted in 68 patients with chronic allergic diseases without the exacerbation and 23 healthy individuals. The provocative oral test was supplied with 2 mg of titanium dioxide (TiO2) in powder or 2 mg of tartrazine in wheat flour processed at a cooking temperature or in a gelatin capsule containing 0.2 mg of titanium dioxide. The oral fluid and/or venous blood were taken up on an empty stomach and 40 minutes after the test. The peroxidase activity of oral fluid and the expression of CD203c and IgE markers on blood basophils were studied. The blood of 20 patients with allergopathology was incubated for 3 and 24 hours with 0.001% and 0.01% mixture of tartrazine, carmoazine, ponso, sanset, TiO2 solutions with the determination interleukin 17 (IL17) level in the supernatants. Peroxidase activity of oral fluid increased on 30% or more in 30% of cases after tartrazine and wheat flour provocation in patients with allergies (12.5% in healthy persons), 44% - after TiO2 in patients with allergies (22% of cases in healthy individuals), 63% - after tartrazine and TiO2 in the white gelatin capsule in patients with allergies (in healthy individuals, p = 0.047). The number of IgE+CD203c+ basophils increased in 44% cases and decreased in 50% cases after provocation with TiO2 in the group of allergic patients, compared with 22% increasing and 22% decreasing in healthy (p = 0.007). A lower concentration of the dye mixture (0.001%) induced IL17 secretion in the supernatant in all 20 patients with allergic diseases, the maximum permissible concentration (0.01%) of the dyes solution - less often in 40% of the examined (p = 0.0002). Secretion of IL17 under the influence of the both concentrations was higher than in the control samples (p <0.05). Thus, the dyes of food and drugs show immunomodulatory activity in patients with allergic diseases (more often) and in healthy individuals. The connection of a positive provocation test with food dyes tartrazine and titanium dioxide with oral fluid peroxidase activity increasing and the number of IgE+CD203c+ basophils and IgEbright basophils increasing and IL17 secretion under the influence of these dyes was found.